2021
DOI: 10.21037/qims-20-1084
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the degree of brain edema regression and changes in cognitive function in patients with recurrent glioma treated with bevacizumab and temozolomide

Abstract: Background: This retrospective study aims to assess the impacts on cognitive status and quality of life in recurrent high-grade glioma patients treated with temozolomide (TMZ), either alone or in combination with bevacizumab (BEV), and explore the relationship between the brain edema regression, BEV use, and cognitive status.Methods: A total of 125 patients with recurrent high-grade glioma were enrolled in this study, of which 65 patients were treated with BEV (5-10 mg/kg IV every 2 weeks) plus TMZ (200 mg/m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In the process of postoperative radiation therapy for glioma, it is easy to cause brain damage (56). As it usually occurs weeks to months after radiotherapy (8,57), PsP is difficult to distinguish from tumor recurrence (58).…”
Section: Discussionmentioning
confidence: 99%
“…In the process of postoperative radiation therapy for glioma, it is easy to cause brain damage (56). As it usually occurs weeks to months after radiotherapy (8,57), PsP is difficult to distinguish from tumor recurrence (58).…”
Section: Discussionmentioning
confidence: 99%
“…The individual symptom profile is also associated with the anatomical region being affected and takes the post-therapeutic tumor burden (biopsy, partial resection) into account. Remaining tumor causes brain edema, tumor hemorrhage, and metabolic changes, which might lead to headache, seizures, fatigue, cognition disturbances, and depression [19,20]. Furthermore, neurological and performance deficits in our study measured by the NIH-SS and the KPS may interfere with the nonphysical symptoms reported by a given patient.…”
Section: Discussionmentioning
confidence: 71%
“…The map highlighted the left peri -sylvian region that was one of the regions predictive in stroke. A link between oedema and cognitive function has been described in relation to radiotherapy treatment ( Wang et al, 2021 ). Recently, we showed abnormal functional connectivity in cortical regions remote from the tumor core, but presumably connected to it by anatomical fibers that travel through the surrounding oedema region ( Silvestri et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%